Pengaruh Efikasi Diri Terhadap Perilaku Kewirausahaan Pada Penyandang Disabilitas di Pulas Katumbiri Bandung - Nugraha, Imam Rizki; Fauziyah, Azizah; Rachmani, Nizza Nadya (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the description of self-efficacy empowerment and how self-efficacy influences entrepreneurial behavior in people with disabilities in Pulas Katumbiri Bandung (PUKA). The object of this study is PUKA Bandung which accommodates people with disabilities to increase their self-confidence so that they are able to socialize and be appreciated by the community. This study uses a quantitative method with a descriptive and verification approach, a sample of 18 people included in the categories of disability one and two, taken through a purposive sampling technique. In people with disabilities in PUKA, self-efficacy with entrepreneurial behavior has a positive and significant influence of 61.5%, based on the results of simple linear regression and t-test. Other variables such as education, interest, and motivation have an influence of 38.5%.